The Differential Contribution of Self-Determination Motivation to Work-Level Versus Organization-Level Behaviors - Niyomsin, Snitnuth (ABAC ODI JOURNAL Vision. Action. Outcome, 2018)
This study aimed to extend self-determination motivation research in work settings (why we work) by examining the antecedents of each of the motivation types and exploring how each type of the motivation contribute to behaviors in view of the work and organizational perspective. The four types of motivation included in the study were intrinsic motivation, identified regulation, introjected regulation, and external regulation. The antecedents of the four types of the motivation were reviewed and found to be an association between the self, the work itself, and the organization’s role. Based on these antecedents, it was hypothesized that each of the motivation types would have differential effects on work-level (passion for work) and organization-level (loyal boosterism) behaviors. Four hundred and forty-three full-time workers, employed by organizations in Bangkok responded to the questionnaires. PLS-SEM was employed to test the hypotheses. Results showed intrinsic motivation and introjected regulation both contributed to work-level behavior (passion for work), with introjected regulation contributing more weight. For organization-level behavior, intrinsic motivation and identified regulation were found to contribute to loyal boosterism, with more weight from intrinsic motivation. External regulation, for the model tested, however, had no contribution to both of the work-level and organization-level behaviors. Theoretical contributions and practical implications are discussed.